2021
DOI: 10.1186/s12889-021-10952-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precarious work on symptomatology of anxiety and depression in Chilean workers, a cross sectional study

Abstract: Background Precarious work is a broad definition for non-standard employment, often including unstable and insecure positions where workers permanently experience uncertainty; these types of jobs are growing steadily around the planet. Since the coup d’état in 1973, Chile has experienced a series of structural economic changes framed by neoliberal ideas cemented in the “Constitution of Pinochet.” Precarious work in Chile is a direct consequence of these ideas. This multidimensional phenomenon h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
4
0
4
Order By: Relevance
“…Cadenas (2016) señaló que el paradigma funcionalista ha sido el enfoque dominante en el management, tanto en las escuelas de negocio como en las decisiones de los directivos. Consecuencia de ello es que para lograr más rentabilidad, a muchos gerentes no les importa contaminar ríos, hacer competencia desleal o pagar bajos salarios (Martino, 2022) (Hernández, 2021) (Bhattacharya & Ray, 2021;López et al, 2021). Tal como se indicó en la "Introducción", el dolor que se investigó no es fisiológico sino ese malestar, desazón, estrés o sufrimiento que un sujeto puede identificar a causa de su trabajo ligado a una organización.…”
Section: El Dolor En La Organizaciónunclassified
See 1 more Smart Citation
“…Cadenas (2016) señaló que el paradigma funcionalista ha sido el enfoque dominante en el management, tanto en las escuelas de negocio como en las decisiones de los directivos. Consecuencia de ello es que para lograr más rentabilidad, a muchos gerentes no les importa contaminar ríos, hacer competencia desleal o pagar bajos salarios (Martino, 2022) (Hernández, 2021) (Bhattacharya & Ray, 2021;López et al, 2021). Tal como se indicó en la "Introducción", el dolor que se investigó no es fisiológico sino ese malestar, desazón, estrés o sufrimiento que un sujeto puede identificar a causa de su trabajo ligado a una organización.…”
Section: El Dolor En La Organizaciónunclassified
“…Tal como se indicó en la "Introducción", el dolor que se investigó no es fisiológico sino ese malestar, desazón, estrés o sufrimiento que un sujeto puede identificar a causa de su trabajo ligado a una organización. Un ejemplo de estos malestares es lo que Han (2020) denomina la presión para producir, mientras que otros dolores devienen de la precariedad en el trabajo (Sharma, 2022;Palma-Vasquez et al, 2022;López et al, 2021;Haro et al, 2020).…”
Section: El Dolor En La Organizaciónunclassified
“…Bhattacharya y Ray (2021) encontraron en su estudio que los trabajadores que demostraban mayor precariedad eran más propensos a experimentar más incapacidades debido a problemas sociales. Asimismo, López et al (2021) analizaron los efectos del trabajo precario en temas como la ansiedad y la depresión en trabajadores chilenos. Otros estudios en este campo son los de Haro Jiménez (2020) y Kawada (2018) en los que se revelan los síntomas de depresión vinculados directamente a las lógicas del denominado trabajo temporal.…”
Section: / 29unclassified
“…Further, global research has found that women, older workers, low‐income workers, and people of color have faced more significant job losses—another harbinger of stress—than their peers (Crayne, 2020; Dang and Viet Nguyen, 2021; Kantamneni, 2020; Saenz and Sparks, 2020). As research has consistently found that uncertainty and precarious working conditions harm mental health (Glavin, Bierman, and Schieman, 2021; Karl et al., 2020; Lopez et al., 2021), those who have faced uncertainty in the last two years may be especially at risk of stress both on the job and more holistically. Furthermore, adverse mental health stressors associated with work precarity can relate to physical health consequences in the long term—such as an increased risk of heart disease, for example (Ahn et al., 2019).…”
Section: Introductionmentioning
confidence: 99%